Validación del IPP-R con alumnos de cuarto y quinto grado de secundaria de colegios públicos y privados de Lima metropolitana - Olivera Guzmán, Cipriano (2013)
The purpose of this research project was to standardize and validate the Revised Professional Interests and Preferences Inventory (IPP-R 2010) in metropolitan Lima on the basis of studies on human development data provided by Unesco in 2007. The population sample consisted of 1567 female and male students attending 4th and 5th year of secondary education in private and public schools. We carried out a descriptive calculus based on the characteristics of the sample, calculated internal consistency based on Cronbach Alpha score, Construct Validity through KMO, the significance value of Bartlett esfericity test, item-test correlations and factor analysis.